2017
DOI: 10.1371/journal.pone.0180428
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the protein half-life in tissue from its cellular properties

Abstract: Protein half-life is an important feature of protein homeostasis (proteostasis). The increasing number of in vivo and in vitro studies using high throughput proteomics provide estimates of the protein half-lives in tissues and cells. However, protein half-lives in cells and tissues are different. Due to the resource requirements for researching tissues, more data is available from cellular studies than tissues. We have designed a multivariate linear model for predicting protein half-life in tissue from its cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…1c ). Along the same lines, a recent work that has analyzed the variables that can predict protein lifetimes in vivo has revealed that protein lifetimes measured in vitro hold the highest predicting power 47 , suggesting that for some homeostasis parameters there are intrinsic similarities that are conserved both in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…1c ). Along the same lines, a recent work that has analyzed the variables that can predict protein lifetimes in vivo has revealed that protein lifetimes measured in vitro hold the highest predicting power 47 , suggesting that for some homeostasis parameters there are intrinsic similarities that are conserved both in vitro and in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…This would allow us to use machine learning to integrate RNA expression and protein turnover ratios in the way that would most accurately predict protein expression in the same tissue 35 , 36 . A more complex relationship undoubtedly exists between these factors, so training a model to more accurately predict this relationship would be highly beneficial 10 12 . It would also be useful to expand the number and variety of protein turnover ratios to put into this model.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we propose a novel method of using protein turnover ratios to infer protein abundance from RNAseq and microarray data, thereby extending its functional value. Every protein has a particular half-life, and therefore exists in a cell to exert its functions for a relatively predictable amount of time 9 , 10 . We propose that using this information about protein half-life in tandem with transcriptomics data could offer insights into protein abundance.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow us to use machine learning to integrate RNA expression and protein turnover ratios in the way that would most accurately predict protein expression in the same tissue [35,36]. A more complex relationship undoubtedly exists between these factors, so training a model to more accurately predict this relationship would be highly beneficial [10][11][12]. It would also be useful to expand the number and variety of protein turnover ratios to put into this model.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Here, we propose a novel method of using protein turnover ratios to infer protein expression from RNAseq and microarray data. Every protein has a particular half-life, and therefore exists in a cell to exert its functions for a relatively predictable amount of time [9,10]. We propose that using this information about protein half-life in tandem with transcriptomics data could offer insights into protein expression.…”
Section: Introductionmentioning
confidence: 99%